Acute respiratory distress syndrome and acute myocarditis developed in a previously healthy adult with influenza B. Issue 1 (December 2016) - Chang, Hsu-Liang; Hsu, Jui-Feng; Tsai, Ying-Ming; Lin, Shang-Yi; Kuo, Hsuan-Fu; Yang, Chih-Jen
Abstract Background Influenza B virus infection is generally considered to be mild and is rarely associated pulmonary cardiovascular involvement in adults. However fatal complications may occur. Case presentation A 43-year-old previously healthy Taiwanese male came to our emergency department due to high fever, chills, general malaise and myalgia for about 4 days. An influenza rapid test from a throat swab was negative. Chest radiography showed mild left lung infiltration and levofloxacin was prescribed. However, progressive shortness of breath and respiratory failure developed 48 h later after hospitalization. Emergent intubation was performed and he was transferred to the intensive care unit where oseltamivir (Tamiflu, Roche) 75 mg orally twice daily was given immediately. In the intensive care unit, cardiac catheterization revealed normal coronary arteries. However, a markedly elevated cardiac enzyme level (Troponin I level was up to 71.01 ng/ml), a positive cardiac magnetic resonance imaging findings and no coronary artery stenosis led to the diagnosis of acute myocarditis. Subsequent real-time polymerase chain reaction of endotracheal aspirates was positive for influenza B. His condition gradually improved and he was successfully weaned from the ventilator on day 22. He was discharged without prominent complications on day 35. Conclusion Influenza B infection is not always a mild disease. Early detection, early administration of antiviral agents, appropriate antibiotics and best supportive care, is still the gold standard for patients such as the one reported.